The gathering - Armstrong, Kelley (Armstrong, Kelley. Darkness rising, 2012)
Sixteen-year-old Maya suspects there may be a relationship between her paw-print birthmark, her connection with wild animals, and strange events occurring in her tiny Vancouver Island community, where a medical research facility harbors big secrets.